(untitled) (GUB Journal of Science and Engineering, 2020)
The electric vehicle (EV) charging systems employ dc-dc power converters as EV chargers. Currently, the expected high penetration of electric vehicle (EV) demands for the integration of the renewable energy sources (RES) into the electric vehicle charging system as a promising solution to cut down the load on the electrical grid. These systems interface with RES by implementing dc-dc power converters. Moreover, with the advent of high-power dc charging, the charging efficiency is largely dependent on the performance of the power converters. Hence, to improve the charging, the soft switching dc-dc converters are implemented to maintain low switching losses and to achieve high-efficiency operation. This paper reviews the non-isolated, soft switching dc-dc power converters for EV charging application. For this purpose, different types of soft switching topologies, namely the snubber, the series resonant, the shunt resonant and the pulse frequency modulated converters are investigated. The advantages and the disadvantages associated with these converters are highlighted. Furthermore, to perform a comparative evaluation, the topologies are simulated in a standard simulation platform. Consequently, the relative standing of the converters depending on several parameters, i.e. the component count, the output voltage and current ripple, the soft switching range, and the power losses are established. Finally, based on these results, the optimum applicability of the converters in the EV charging application is determined. GUB JOURNAL OF SCIENCE AND ENGINEERING, Vol 6(1), Dec 2019 P 60-74